The contribution of Sanggar Siradjuddin Gowa as a Developer of Traditional Dance Arts in the Context of Community-Based Arts Education - Andi Tenri Juli Astari; Agus Cahyono; Malarsih Malarsih (Universitas Muhammadiyah Enrekang, 2023)
Abstract This research is motivated by the activities of members of the siradjuddin studio in gowa district, who have made various contributions as developers of traditional dance arts in the context of community-based arts education. This research was carried out to support arts and culture education and the inheritance of cultural traditions in a district . This type of research uses an interdisciplinary approach consisting of the disciplines of Ethnochoreology and Arts Education using qualitative methods based on case studies. The results of the research show that the contribution of the Gowa Siradjuddin Studio as a developer of traditional dance arts in the context of community-based arts education consists of three, namely (1) the contribution of the Siradjuddin Gowa Studio as a manager of non-formal arts education (educational contribution), (2) the contribution of the Siradjuddin Gowa Studio as an arts developer. traditional dance (conservative contribution), (3) contribution of the Siradjuddin Gowa studio as a creative industry player. Keywords: Contribution , Traditional Art , Community Based Arts Education . ABSTRAK Penelitian ini dilatarbelakangi oleh kegiatan anggota Sanggar Siradjuddin Kabupaten Gowa yang telah memberikan berbagai kontribusinya sebagai pengembang seni tari tradisional dalam rangka pendidikan seni berbasis masyarakat. Penelitian ini dilakukan untuk mendukung pendidikan seni budaya dan pewarisan tradisi budaya di kabupaten Gowa. Jenis penelitian ini menggunakan pendekatan interdisiplin yang terdiri dari disiplin ilmu Etnokoreologi dan Pendidikan Seni dengan menggunakan metode kualitatif berdasarkan studi kasus. Hasil penelitian menunjukkan bahwa kontribusi Sanggar Siradjuddin Gowa sebagai pengembang seni tari tradisional dalam rangka pendidikan seni berbasis masyarakat terdiri dari tiga, yaitu (1) kontribusi Sanggar Siradjuddin Gowa sebagai pengelola pendidikan seni non formal (Kontribusi Edukatif), (2) kontribusi Sanggar Siradjuddin Gowa sebagai pengembang seni tari tradisional (kontribusi konservatif), (3) kontribusi sanggar Siradjuddin Gowa sebagai pelaku industri kreatif.Kata Kunci : Kontribusi, Seni Tari Tradisional, Pendidikan Seni Berbasis Masyarakat.